Transgender and Gender Non-Conforming College Students’ Challenges, Supports, and Successes: An Interpretative Phenomenological Analysis - Jennifer R. Curry; Imre Csaszar; Tiffany Shierling (Georgia Journal of College Student Affairs, 2023)
We report findings from an interpretative phenomenological analysis (IPA) study of transgender and gender non-conforming (TGNC) participants’ perceptions of their on-campus experiences. Participants reported their lived experiences of campus culture in the Deep South. The data was viewed through a minority stress framework. Four major themes emerged: a) supports for students; b) barriers for students; c) undergoing personal change; and d) influencing systemic change.